PHOTOCATALYTIC DEGRADATION OF METHYLENE BLUE USING ZINC OXIDE NANOPARTICLES - Ho Thi Ngoc Suong; Nguyen Hung Thuy; Nguyen Thi Thuy Linh; Nguyen Vien Tuong (HUIT Journal of Science, 2023)
Zinc oxide nanoparticles were synthesized by a simple sol-gel method with Zinc acetate dihydrate as the precursor. The photocatalyst structure was characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The catalyst was synthesized at 400-700 °C calcination conditions, the results show that the zinc oxide nanocrystal size is 22 - 32 nm, highly effective in photocatalysis, the decomposition of methylene blue. Their photocatalytic activities for methylene blue degradation were evaluated in a batch reactor under simulated visible light using a special 26 W compact lamp. The highest photocatalytic activity for methylene blue degradation was observed at 400 °C, resulting in 95.1% photocatalytic degradation yield after 4 h under visible light irradiations.